ERYTHROCYTE FATTY ACID ABERRATIONS IN AMYOTROPHIC LATERAL SCLEROSIS – CORRELATION WITH DISEASE DURATION: Fatty acid alterations in ALS - Minic, Rajna; Arsic, Aleksandra; Kojadinovic, Milica; Palibrk, Aleksa; Djordjevic, Brizita; Stević, Zorica (Journal of Medical Biochemistry, 2023)
Background: Recent literature data highlights the presence of metabolic changes in amyotrophic lateral sclerosis (ALS). To explore possible early metabolic changes, we aimed to analyze the fatty acids (FA) composition of erythrocytes in newly diagnosed ALS patients and to see whether fatty acid levels correlate with the ALSFRS-R score or disease duration. Methods: The severity of motor function involvement was assessed by the ALSFRS-R scale at the initial evaluation. The study comprised 26 clinically diagnosed ALS patients, mean ALSFRS-R 38±8. Control group included 26 healthy volunteers. Fatty acid profile of erythrocyte membranes was analyzed by gas-liquid chromatography. Results: Significantly higher levels of palmitic acid and total saturated FAs were detected in ALS patients. Total monounsaturated FA, palmitoleic, vaccenic and oleic acid were also significantly increased in ALS patients. The levels of eicosapentaenoic acid, docosapentaenoic acid, total polyunsaturated FA (PUFA) and n-6 PUFA were significantly lower in ALS patients. Additionally, α-linolenic acid, the precursor of n-3 PUFA family, was not detected in ALS patients at all. We found no significant correlation between the ALSFRS-R score and the abundance of individual FAs analyzed. Moderate negative correlation was found between disease duration and DHA level and positive correlation was detected with MUFA. Conclusions: Experimental evidence presented may contribute to the shaping of a beneficial nutritional intervention.